2021
DOI: 10.51724/ijpce.v13i3.216
|View full text |Cite
|
Sign up to set email alerts
|

Views of Prospective Chemistry Teachers on the Use of Graphic Organizers Supported with Interactive PowerPoint Presentation Technology in Teaching Electrochemistry Concepts

Abstract: The purpose of this study is to evaluate the views and experiences of the prospective chemistry teachers (PCTs) about the use of graphic organizers (GOs) supported with interactive PowerPoint presentation technology in teaching electrochemistry concepts. Ten GOs were developed and a pair of slides for all of them which contains partial and complete versions of the GOs was constructed. Participants of this study consisted of two different study groups. The preliminary trial of the study was carried out with fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Among the establishment purposes of science high schools should be a resource for the training of students as scientists. Thus, although both programs contain the same units, topics, and the order of units and topics, the content is given in a little more detail in science high schools, and science high school programs include more experimental work for students (Nakibog ˘lu, 2021).…”
Section: The Turkish Contextmentioning
confidence: 99%
“…Among the establishment purposes of science high schools should be a resource for the training of students as scientists. Thus, although both programs contain the same units, topics, and the order of units and topics, the content is given in a little more detail in science high schools, and science high school programs include more experimental work for students (Nakibog ˘lu, 2021).…”
Section: The Turkish Contextmentioning
confidence: 99%
“…For this reason, it can be suggested that chemistry concepts are related to macroscopic and microscopic levels, that most of them benefit from symbolic representations in expressing these relationships, and that those teaching models, methods, and techniques based on the constructivist learning approach should be used in chemistry teaching. In addition, including visual materials such as graphic organizers can help students establish easier and more accurate relationships in the knowledge structure …”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…In addition, including visual materials such as graphic organizers can help students establish easier and more accurate relationships in the knowledge structure. 88 As stated in the framework for K-12 science education, it was seen that students' abilities to comprehend the interactions of matter and energy are at the center of their science education. 50 For this reason, it is very important for tomorrow's chemistry teachers to have a master of these subjects, as they are directly related to their classroom teaching.…”
Section: ■ Limitations and Recommendationsmentioning
confidence: 99%
“…Using GOs in chemistry textbooks can both increase the active participation of students and contribute to the development of high-level thinking skills (Nakiboğlu and Nakiboğlu, 2021;Nakiboğlu, 2021). Based on these considerations, the following suggestions can be made regarding the use of GOs in chemistry textbooks and the use of GOs in lessons in general.…”
Section: Nakiboğlumentioning
confidence: 99%